Climate change and health within the South African context: A thematic content analysis study of climate change and health expert interviews - (:unkn) unknown (My University, 2022)
Background: Climate change presents an unprecedented and urgent threat to human health and survival. South Africa’s health response will require a strong and effective intersectoral organisational effort.Aim: Exploratory interview outcomes are used to advance practice and policy recommendations, as well as for broad input in the development of a draft national framework for a health risk and vulnerability assessment (RVA) for national departments.Setting: Nationally in South Africa.Method: Twenty key expert interviews were conducted with South African experts in the field of climate change and health. Interview data was analysed by means of thematic content analysis.Results: Findings suggest that previously poor communities are most at risk to the impacts of climate change on health, as well as those with underlying medical conditions. Climate change may also serve as a catalyst for improving the healthcare system overall and should serve as the conduit to do so. A draft climate change and health RVA should take into account existing frameworks and should be implemented by local government. It is also critical that the health and health system impacts from climate change are well understood, especially in light of the plans to implement the (South African) National Health Insurance (NHI) scheme.Conclusion: Practice and policy initiatives should be holistic in nature. Consideration should be given to forming a South African National Department of Climate Change, or a similar coordinating body between the various national departments in South Africa, as health intercepts with all other domains within the climate change field.
Keywords: African Research